Metaética e fundamentação dos direitos humanos: uma análise expressivista - Bisol, César (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation investigates the basis of human rights against the background of moral language. From a reading of metaethics, in which the aspect of moral expressivism stands out, we seek to explain the foundation through the analysis of Allan Gibbard and his expressivist theory. The research uses the expressivist metaethical method and follows the analytical philosophy's differentiation guideline between ethics and metaethics, namely between moral discourse and philosophy about the discourse of morality, or between moral statements and statements about moral statements. The aim is to arrive at a clear understanding of the nature of morality regarding human rights and the relationship between the reasons for a moral commitment. In this way, with the possibility of appropriating metaethical studies to analyze human rights, the central problem of this research seeks to answer the following question: can Allan Gibbard's expressivist theory of the norm support the legal nature of human rights? Aiming to achieve the research objective, the first step aims to investigate the link between human rights and moral rights, which will enable subsequent analysis of metaethics, since the moral nature of human rights will be examined. Thus, in the third part, it is concluded that a metaethical approach supported by normative expressivism can be the central point for the foundation of human rights. The path taken in the previous points presents itself as a justification for the analysis of the present work, which aims to seek a foundation for human rights that is not the same as the common thinking of positive law. As human rights have moral characteristics and, therefore, are part of moral discourse, they must be considered moral to the extent that they pursue the firm purpose of attributing a notion of universality to the highest values of human existence.
Keywords: Direitos humanos; Direitos morais; Metaética; Expressivismo moral; Human rights; Moral rights; Metaethics; Moral expressivism; ACCNPQ::Ciências Sociais Aplicadas::Direito